(untitled) (Global Journal of Medical Research, 2022)
Peritoneal hydatidosis is a rare and poorly known hydatid disease Acute cyst rupture into the peritoneal cavity is one of its complications We report a clinical case of a 25-year-old patient admitted to the emergency department for acute abdominal pain the final diagnosis was acute peritonitis caused by the rupture of hydatid cyst into the peritoneal cavity associated with hepatic hydatidosis